2022
DOI: 10.3389/fmicb.2021.812591
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter in Wild Birds: Is It an Animal and Public Health Concern?

Abstract: Campylobacteriosis continues to be one of the leading causes of foodborne bacterial zoonotic infections worldwide. Despite its public health importance, the status of this disease in wild birds and the possibility of transmission from wild birds to domestic animals and humans have not been clearly elucidated yet. This article reviews the available literature with the aim of making a comprehensive manuscript on this disease status in wild birds and the possibility of interspecies transmission. Campylobacter has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 103 publications
(233 reference statements)
1
33
0
2
Order By: Relevance
“…The host lability of Campylobacter spp. and their ability to overlap between humans, domestic animals, and wild birds further highlights the public health concern generated by the ability of wild birds to mobilize these strains across large geographic distances [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host lability of Campylobacter spp. and their ability to overlap between humans, domestic animals, and wild birds further highlights the public health concern generated by the ability of wild birds to mobilize these strains across large geographic distances [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Any environment frequented by wild birds, and waterfowl specifically, could contain a diverse array of Campylobacter spp. (for review see [ 10 ]). Sanitation District No.…”
Section: Introductionmentioning
confidence: 99%
“…C. jejuni and C. coli from livestock, including poultry, pigs, and ruminants, and their feed have shown high rates of antibiotic resistance, while C. coli appears to be better adapted for MDR [25]. Worldwide, Campylobacter has been isolated from various wild bird species and wild boars, with a MDR rate of 67.0% for C. coli from wild boars [1,26 ▪ ]. A recent study on the presence and characteristics of Campylobacter spp.…”
Section: Prevalence Of Antimicrobial Resistant Campylobactermentioning
confidence: 99%
“…Campylobacteriosis is the most commonly reported zoonotic bacterial foodborne gastroenteritis [1]. The European Food Safety Authority (EFSA) and the Centers for Disease Control and Prevention (CDC) have reported that Campylobacteriosis is one of the leading causes of human bacterial diarrhea in the European Union and United States [2 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…The number and diversity of Campylobacter transiting in animal and environmental compartments is immense [ 3 , 4 ]. Wild birds are hypothesized to act as wildlife reservoirs of Campylobacter jejuni , causing fecal contamination of the environments, of food production farms, and possibly transmitting Campylobacter to livestock, domestic animals as well as to humans [ 5 ]. Aside from being confirmed in more than 80% of campylobacteriosis cases, C. jejuni is also the most frequently detected species in several wild bird species [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%